If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(2x + -1) = y Reorder the terms: (1 + 2x)(2x + -1) = y Reorder the terms: (1 + 2x)(-1 + 2x) = y Multiply (1 + 2x) * (-1 + 2x) (1(-1 + 2x) + 2x * (-1 + 2x)) = y ((-1 * 1 + 2x * 1) + 2x * (-1 + 2x)) = y ((-1 + 2x) + 2x * (-1 + 2x)) = y (-1 + 2x + (-1 * 2x + 2x * 2x)) = y (-1 + 2x + (-2x + 4x2)) = y Combine like terms: 2x + -2x = 0 (-1 + 0 + 4x2) = y (-1 + 4x2) = y Solving -1 + 4x2 = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4x2 = 1 + y Combine like terms: -1 + 1 = 0 0 + 4x2 = 1 + y 4x2 = 1 + y Divide each side by '4'. x2 = 0.25 + 0.25y Simplifying x2 = 0.25 + 0.25y Reorder the terms: -0.25 + x2 + -0.25y = 0.25 + 0.25y + -0.25 + -0.25y Reorder the terms: -0.25 + x2 + -0.25y = 0.25 + -0.25 + 0.25y + -0.25y Combine like terms: 0.25 + -0.25 = 0.00 -0.25 + x2 + -0.25y = 0.00 + 0.25y + -0.25y -0.25 + x2 + -0.25y = 0.25y + -0.25y Combine like terms: 0.25y + -0.25y = 0.00 -0.25 + x2 + -0.25y = 0.00 The solution to this equation could not be determined.
| -2(z+3)-z+-z-4(z+2)= | | 2x+84=3.333333333 | | 0+.75x=7.5+.5x | | 2x+84=3 | | (2/3)t=9 | | 6b-3b+4b+1=25 | | -3g-3= | | -8+3u=-6+5u-8 | | -5.8(2p+4)-1.6(3p-5)= | | 2x+1+y=5y+7x+11 | | 1.90=3(.25q)+3 | | 45x-29x-7x+2x-x=30 | | 1.90=.75q | | 12n+7=8n+16 | | 1.90=.75q+3 | | 6x-6x-4=4 | | 1=(x/25) | | x/14=21 | | 7.5+.5x=15 | | 32a+5=52a+13 | | 5t^2+36=18 | | 4x-4x=3 | | 11.7/3 | | -10k+6-8k=-2k-10 | | 2x-12=4x-52 | | 16=x+21 | | 7d+4d-6d-d-4=4 | | (2h-1000)=4000 | | 4b+16=-10b+44 | | (n-1)(n-6)=0 | | 3(1/2)-5y=-36 | | 3q+20=32 |